2019
DOI: 10.1186/s12985-019-1231-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying novel biomarkers of the pediatric influenza infection by weighted co-expression network analysis

Abstract: Background: Despite the high yearly prevalence of Influenza, the pathogenesis mechanism and involved genes have not been fully known. Finding the patterns and mapping the complex interactions between different genes help us to find the possible biomarkers and treatment targets. Methods: Herein, weighted gene co-expression network analysis (WGCNA) was employed to construct a co-expression network among genes identified by microarray analysis of the pediatric influenza-infected samples. Results: Three of the 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…Along these lines, GCNs are also considered suitable for the study of infectious diseases, as those caused by viruses to the matter at hand [ 38 ]. To do so, multiple studies have analyzed the effects of viral infection over the organism, focusing on immune response or tissue damage [ 39 , 40 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, GCNs are also considered suitable for the study of infectious diseases, as those caused by viruses to the matter at hand [ 38 ]. To do so, multiple studies have analyzed the effects of viral infection over the organism, focusing on immune response or tissue damage [ 39 , 40 ].…”
Section: Related Workmentioning
confidence: 99%
“…Using several network-based approaches on multiple knockout mouse strains, authors found that ranking genes based on their network topology made accurate predictions of the pathogenic state, thus solving a classification problem. In [ 39 ], co-expression networks were generated by microarray analysis of pediatric influenza-infected samples. Thanks to this study, genes involved in the innate immune system and defense to virus were revealed.…”
Section: Related Workmentioning
confidence: 99%
“…Although RTP4 was initially characterized as a GPCR chaperone protein as described above ( Saito et al, 2004 ; Behrens et al, 2006 ; Mainland and Matsunami, 2012 ), more recent publications clearly revealed its significant role in regulation of immune responses such as IFN-related antiviral immunity ( Schoggins et al, 2011 ; Nair et al, 2017 ; Dang et al, 2018 ; Zarei Ghobadi et al, 2019 ; He et al, 2020 ). Thus, it is suggested that RTP4 could be induced by type I IFNs and work as a negative regulator of interferons pathways.…”
Section: Possible Physiological Role Of Rtp4 In Pain Perception – Thementioning
confidence: 99%
“…Coronavirus and influenza are pathogens causing severe respiratory illness to humans 14 . Recent reports demonstrated that SP110, HERC5, SAMD9L, RTP4, ESPT11 genes were identified to control and improve the immune system and defense mechanism against influenza by network analysis 15 . It has the supremacy to act as biomarkers and targets for pediatric influenza mediated therapy.…”
Section: Introductionmentioning
confidence: 99%